Short-term regression of corneal neovascularization with combination therapy of argon green laser photocoagulation and subconjunctival bevacizumab - Anand, Nandita (Int Med Case Rep J, 2019)
We present a case of a 49 year-old male with history of corneal neovascularization secondary to herpes zoster keratitis that clinically and subjectively improved for approximately 4 months after treatment with argon laser photocoagulation to feeder vessels and subconjunctival bevacizumab. This is the first report in the literature that describes this novel combination treatment for corneal neovascularization in the setting of varicella-zoster virus and discusses its efficacy.